Проблемы и перспективы внедрения дистанционного образования Украины - Возняк, А. Б. (БНТУ, 2011)
Distance learning contributes to the basic principles of educational policy — oriented training and education to the individual development of personality, satisfaction, and the formation of its intellectual needs and interests in accordance with the public interest. The paper analyzes the opportunities and prospects for implementation of distance education in national education, the realization of a system of continuous education in Ukraine.